2021
DOI: 10.21037/atm-21-2701
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin exerts a protective effect on murine knee chondrocytes treated with IL-1β through blocking the NF-κB/HIF-2α signaling pathway

Abstract: Background: Osteoarthritis (OA) is characterized by erosion and degradation of articular cartilage. This study assessed the effects of curcumin on mouse knee cartilage chondrocytes. Methods: Chondrocytes were treated for 24 hours with interleukin IL-1β (10 ng/mL) alone, or the combination of curcumin (10, 20, and 50 μM) and IL-1β. The proliferation, viability, and cytotoxicity of the chondrocytes were evaluated by the MTS assay. Expression of SOX9, AGG, Col2α, MMP9, ADAMTS5, COX2, iNOS, pIκB-α, pNF-κB, and hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Curcumin is the most researched type of curcuminoid due to its potent antioxidant, anti-inflammatory, antimicrobial, antirheumatic, neuroprotective, anticancer, hepatoprotective, and cardioprotective properties [ 68 ]. Several studies have reported the pain-alleviating properties and the chondroprotective effects of curcumin and curcuminoids in clinical, in vivo, and in vitro studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
See 3 more Smart Citations
“…Curcumin is the most researched type of curcuminoid due to its potent antioxidant, anti-inflammatory, antimicrobial, antirheumatic, neuroprotective, anticancer, hepatoprotective, and cardioprotective properties [ 68 ]. Several studies have reported the pain-alleviating properties and the chondroprotective effects of curcumin and curcuminoids in clinical, in vivo, and in vitro studies [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( Table 1 ).…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
“…Another in vitro study also confirmed the anti-inflammatory effects of curcumin, where IL-1β-induced inflammation was reduced and the mRNA expression of COL-II and SOX9 in chondrocytes were downregulated. Further immunofluorescence and immunohistochemistry studies revealed that curcumin drastically reduced the activation of NF-κB/HIF-2α in IL-1β-induced chondrocytes [ 64 ].…”
Section: Efficacy and Mechanism Of Action Of Polyphenolsmentioning
confidence: 99%
See 2 more Smart Citations
“…With regard to chronic musculoskeletal disorders, such as RA, osteoporosis, or OA, various polyphenols have been found to reduce inflammation and, in addition, exhibit tissue-protective and regeneration-stimulating effects [ 36 , 92 , 93 , 125 ] due to their ability to modulate dysregulated pro-inflammatory pathways back to physiological conditions, and, more so, to stimulate anabolic processes in the respective tissues, helping them to regenerate and heal [ 36 , 126 , 127 , 128 , 129 ]. Additionally, in tendinitis, as a very common and painful condition disabling musculoskeletal functionality and still lacking sustainable treatment, various plant-derived compounds have been demonstrated to affect inflammation and promote tissue healing, thus representing promising bio-active treatment agents in tendinitis therapy [ 10 , 14 , 36 , 62 , 65 , 130 , 131 , 132 , 133 ].…”
Section: Plant-derived Nutraceuticals In the Treatment Of Tendinitismentioning
confidence: 99%